What are the drivers behind the growing popularity of farmers' markets in the Western Cape? - Biesenbach, Rinette (The IIE, 2016)
The aim of this study is to examine the increasing popularity of the use of farmers’ markets as a form of retail. The study will attempt to identify what variables have the biggest influence on why farmers’ markets are becoming increasingly popular. By being aware of the growing popularity of farmers’ markets and the reasons behind it, farmers’ markets can focus on adapting their strategies and products to attract even more consumers and to improve their business. Producers and consumers are showing a renewed, increased interest in farmers’ markets, which could be due to various reasons. This study will examine what those reasons are. There is limited information available on the topic of farmers’ markets in specifically South Africa. Applying the information of other countries to the South African farmers’ market industry could lead to false assumptions and findings. This could be challenging, however it is feasible. In the literature review and questionnaires there was specifically focused on four variables, namely: (1) The conscious consumer – Societal and environmental well being; (2) Organic to local – The food movement; (3) Social benefits and reconnection with producers; and (4) Farmers’ markets as an additional form of retail. Research was done on these topics to get a thorough idea of why these factors are important for consumers. For this study, I assumed that the reason for the growth in the popularity of farmers' markets would be a combination of various factors. The factors that I feel will have the biggest influence, is the increasing interest in buying organic products, that consumers feel farmers' markets is a good opportunity for socialising, and that consumers see markets as another form of retail. In order to be able to make a reliable conclusion and suggestions, the data that I used was collected via secondary research (previous literature), and questionnaires. For my data analysis, all the information that was completed by consumers in the questionnaires was studied. These answers were then converted to pie charts, making it easier to analyse further. The results yielded in the research study could make a useful contribution to the existing literature on possible reasons for the increase in popularity of farmers’ markets. By being aware of the growing popularity of farmers’ markets and the reasons behind it, commercial brands can focus on adapting their strategies and products to prevent consumers from rather buying certain products at vii farmers’ markets instead of commercial brands and stores. After the research study have been completed, and if the results and conclusions can be considered as being valid and reliable, this study could possibly be published in journals such as Food Research International or similar journals. The results are specifically focused on consumers living in the Western Cape, but it could be generalised to other provinces, as the farmers' markets are more or less similar.
Thesis
Keywords: Farmers' markets; Producers; Consumer; Food research; Western Cape